The Effectiveness of Oral Rehydration Solution at Various Concentrations as a Storage Media for Avulsed Teeth - Eskandarian, Tahereh; Badakhsh, Samaneh; Esmaeilpour, Tahereh (Iranian Endodontic Journal, 2013)
Introduction: Following avulsion, the periodontal ligament (PDL) cells are at risk of necrosis. To achieve a favorable survival prognosis, the PDL cells must be kept viability. Therefore, immediate replantation is considered as the treatment of choice and in case it is not possible, storing the tooth in an appropriate storage media should be considered. Oral Rehydration Solution (ORS) is a glucose-electrolyte solution which can keep the optimal osmolality as well as pH and can even provide nutrients which are necessary for cellular growth. The present study aimed to evaluate the effectiveness of different concentrations of ORS in maintaining the viability of the PDL cells at different time points. Materials and Methods: PDL cells were obtained from healthy extracted human premolars. Then, 8×10³ cells were seeded in each well of 96-well plate. Afterwards, each well was treated with ORS in three different concentrations and DMEM for 1, 3, 6, and 9 hours. Cell viability was determined by using the MTT assay. One way-ANOVA and post hoc (LSD) test were used for comparing the study groups. Results: According to the results, 25% and 50% concentrations of ORS were more effective in preserving the PDL cell viability and could maintain 79.98% and 68.34% of the PDL cells, respectively, at least for the last experimental time point (up to 9 hours). Conclusions: Therefore, our findings indicate that ORS might be a suitable storage medium for avulsed teeth.